Media Ajar Berbasis Digital dalam Pembelajaran IPS di SD/MI - Maharani Nurul Ain; Asyifatun Muqaromah; Oman Farhurohman (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The importance of utilizing digital learning resources for Social Studies (IPS) learning at Elementary School (SD) and Madrasah Ibtidaiyah (MI) levels is discussed in this article. The utilization of digital teaching materials is expected to improve IPS learning in a more interesting, dynamic, and efficient way along with technological advances. This study identifies various digital learning media, including web-based learning platforms, educational software, and instructional videos, that can be used in the context of IPS learning. The advantages and difficulties faced by teachers and students when incorporating digital media into the classroom are also discussed in this article. It is hoped that by using a digital approach, students will be able to better understand IPS content and develop 21st-century skills needed for everyday life. In addition, this article offers suggestions for the efficient use of digital learning resources that are appropriate to the needs of MI and elementary school students.